1992
DOI: 10.1021/ja00035a019
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of biological molecules with heparin and related glycosaminoglycans. 1. Identification of a specific heparin binding site for histamine

Abstract: The interaction of histamine with beef lung heparin has been characterized by 'H and I3C NMR spectroscopy. IH chemical shifts provide evidence that histamine forms a complex with heparin both at low pD where 2-Osulfo-a-~-idopyranosyluronic acid (IdoA-2s) residues are in the carboxylic acid form and at higher pD where the carboxyl groups are deprotonated. At low pD, the chemical shift data are consistent with weak delocalized binding of the diprotonated form of histamine by the highly negatively charged polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

1993
1993
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 14 publications
0
28
0
2
Order By: Relevance
“…Recently, an accurate nmr study dealing with the interaction of histamine to heparin has established that the binding of histamine to heparin is site specific, i-e., the ammonium group binds to the carboxylate group, whereas the imidazolium ring is located in a pocket surrounded by three anionic groups, two 0-sulfate groups, and the carboxylate of the following ring. 42 The finding of a binding site Structure of the repeating disaccharide unit with high affinity for the imidazolium ring is of particular interest for the interaction of heparine with histidine-containing peptides, 43 as in the present article.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, an accurate nmr study dealing with the interaction of histamine to heparin has established that the binding of histamine to heparin is site specific, i-e., the ammonium group binds to the carboxylate group, whereas the imidazolium ring is located in a pocket surrounded by three anionic groups, two 0-sulfate groups, and the carboxylate of the following ring. 42 The finding of a binding site Structure of the repeating disaccharide unit with high affinity for the imidazolium ring is of particular interest for the interaction of heparine with histidine-containing peptides, 43 as in the present article.…”
Section: Resultsmentioning
confidence: 91%
“…shown below with the iduronic acid residue (the I ring) in the ~C4 conformation and the glucosamine (the A ring) in the 4C t conformation. Because of its high negative charge density, many biological molecules, including histamine and many peptides and proteins [15,17], bind to heparin. The binding mechanism may be either delocalized (territorial) or site specific electrostatic interactions between anionic sites on heparin and cationic sites on the biological molecules [15].…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we report that GHK binds to the glycosaminoglycan heparin; the binding interaction has been characterized by [IH]NMR spectroscopy and is shown to involve the Nterminal glycyl ammonium, the histidyl imidazolium and the lysine ammonium groups, with the imidazolium group interacting site specifically with the imidazolium-binding site on heparin [17].…”
Section: Introductionmentioning
confidence: 99%
“…We examined the possibility that it could represent the first stages of 'resealing' of the cell (Nielsen et al, 1981;Steyer et al, 1997), but found that pore contraction caused the efflux to decrease at a faster, not a slower rate. There is a difference of about 1.2 pH units between the interior of the vesicle (pH 6.0) and extracellular solution (Johnson et al, 1980) and since binding to heparin, at least for histamine, depends upon pH (Rabenstein et al, 1992) it is expected that D will vary during the release process as the pH gradient equilibrates. In addition, there is evidence that D would increase (not decrease) by about a factor of 2 as the gel expands and the network becomes less tortuous (Krizaj et al, 1996;Rusakov and Kullmann, 1998).…”
Section: Constant Diffusivitymentioning
confidence: 99%